Comparing Hydraulics Between Two Grapevine Cultivars Reveals Differences in Stomatal Regulation Under Water Stress and Exogenous ABA Applications - Dayer, Silvina; Scharwies, Johannes D.; Ramesh, Sunita A.; Sullivan, Wendy; Doerflinger, Franziska C.; Pagay, Vinay; Tyerman, Stephen D. (Frontiers in Plant Science, 2020)
Hydraulics of plants that have different strategies of stomatal regulation under water stress are relatively poorly understood. We explore how root and shoot hydraulics, stomatal conductance (gs), leaf and root aquaporin (AQP) expression, and abscisic acid (ABA) concentration in leaf xylem sap ([ABA]xylemsap) may be coordinated under mild water stress and exogenous ABA applications in two Vitis vinifera L. cultivars traditionally classified as near-isohydric (Grenache) and near-anisohydric (Syrah). Under water stress, Grenache exhibited stronger adjustments of plant and root hydraulic conductances and greater stomatal sensitivity to [ABA]xylemsap than Syrah resulting in greater conservation of soil moisture but not necessarily more isohydric behaviour. Correlations between leaf (Ψleaf) and predawn (ΨPD) water potentials between cultivars suggested a 'hydrodynamic' behaviour rather than a particular iso-anisohydric classification. A significant decrease of Ψleaf in well-watered ABA-fed vines supported a role of ABA in the soil-leaf hydraulic pathway to regulate gs. Correlations between leaf and root AQPs expression levels under water deficit could explain the response of leaf (Kleaf) and root (Lpr) hydraulic conductances in both cultivars. Additional studies under a wider range of soil water deficits are required to explore the possible differential regulation of gs and plant hydraulics in different cultivars and experimental conditions.